The Use of Code-Mixing among Pamonanese in Parata Ndaya Closed-Group Facebook - Luke, Joice Yulinda (Lingua Cultura, 2015)
Research intended to figure out why Pamonanes did code-mixing in Parata Ndaya, a Facebook closed-group site. The research applied qualitative method to get the types of code-mixing and reasons for doing code-mixing, while the analysis used Hoffman’s theory. Data were taken from comments of three active members of Parata Ndaya. Comments selected were mainly focused on political issues that happened during Regional House Representative Election in 2014. Data analysis reveals that code-mixing is mostly found in jokes and some comments about political leaders. Thus, the results can provide insights for Parata Ndaya members to build awareness on preserving their local language (i.e. Pamona language) as well as to enhance solidarity among members of the group site.